2005
DOI: 10.1161/01.hyp.0000159192.93968.8f
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Regulation by the Angiotensin Type 2 Receptor

Abstract: T he renin-angiotensin system is a coordinated hormonal cascade of major importance in cardiovascular and renal regulation. The principle effector of this system is the octapeptide angiotensin II (Ang II), which acts at 2 cell membrane receptors, AT 1 and AT 2 . The majority of the actions of Ang II have been demonstrated to be mediated by the AT 1 receptor, including growth promotion, vasoconstriction, antinatriuresis, aldosterone secretion, salt appetite, thirst, sympathetic outflow and inhibition of renin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 46 publications
(66 reference statements)
5
125
0
5
Order By: Relevance
“…20 Although the vast majority of actions of Ang II are mediated by AT 1 Rs, comparatively little is known regarding the renal actions of AT 2 Rs. 21,22 The AT 2 R is expressed in the adult rat kidney at multiple sites, including proximal and distal tubules, glomeruli, renal blood vessels, juxtaglomerular cells, cortical and medullary collecting ducts, and cortical interstitial cells. 13,23 The role of AT 2 Rs in renal hemodynamic function is largely unknown, although AT 2 Rs have been demonstrated to oppose AT 1 R-mediated vasoconstriction in the renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although the vast majority of actions of Ang II are mediated by AT 1 Rs, comparatively little is known regarding the renal actions of AT 2 Rs. 21,22 The AT 2 R is expressed in the adult rat kidney at multiple sites, including proximal and distal tubules, glomeruli, renal blood vessels, juxtaglomerular cells, cortical and medullary collecting ducts, and cortical interstitial cells. 13,23 The role of AT 2 Rs in renal hemodynamic function is largely unknown, although AT 2 Rs have been demonstrated to oppose AT 1 R-mediated vasoconstriction in the renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is still some controversy about the intracellular pathways controlled by the AT 2 . Most studies agree that Ang II signaling through this receptor activates the serine/threonine phosphatase PP2A, which may direct the signal towards the control of the activity of K + -and Ca 2+ -channels [23,24]. In addition, some studies have suggested that the AT 2 can negatively regulate the AT 1 -dependent activation of the MAP kinase cascade [25].…”
Section: The Signaling System Of Ang IImentioning
confidence: 98%
“…2 The role of the AT 2 receptor is less clearly understood. 3 Furthermore, whereas Ang II has been considered the major effector peptide of the RAS, its direct metabolite, des-aspartyl 1 -Ang II (Ang III) also has biologic activity. 4 Indeed, some actions originally attributable to Ang II, such as vasopressin release, are mediated at least in part by Ang III.…”
mentioning
confidence: 99%